2005
DOI: 10.1097/00001199-200505000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Physical Complaints, Medical Service Use, and Social and Employment Changes Following Mild Traumatic Brain Injury

Abstract: Using a prospective, dual-cohort study design in which selected preinjury factors were controlled, we present outcomes of 235 patients in a case cohort and 235 patients in a comparison cohort following emergency-department-diagnosed mild traumatic brain injury (MTBI). Symptoms, medical services use, and social and employment concerns were evaluated 6 months after the injury. After adjusting for preinjury characteristics, headaches, dizziness, vision difficulties, memory or learning problems, and alcohol intole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 50 publications
2
56
0
2
Order By: Relevance
“…Patients in the MTBI cohort used rehabilitation (23%), counseling (26%), physician (12%) and acute care services (14%) (Kraus et al, 2005). Kraus et al (2005) also found that 82.6% of the MTBI cohort reported one or more symptoms during the 6 months follow up period.…”
Section: Prognosismentioning
confidence: 93%
See 3 more Smart Citations
“…Patients in the MTBI cohort used rehabilitation (23%), counseling (26%), physician (12%) and acute care services (14%) (Kraus et al, 2005). Kraus et al (2005) also found that 82.6% of the MTBI cohort reported one or more symptoms during the 6 months follow up period.…”
Section: Prognosismentioning
confidence: 93%
“…A prospective dual-cohort study by Kraus, Schaffer, Ayers, Stenehjem & Shen (2005) compared patients with a physician-diagnosed MTBI with a comparison cohort of patients with other physician-diagnosed injuries comparable in severity but not involving the head (fractures, contusions, lacerations or strains). Each cohort consisted of 235 patients.…”
Section: Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…Grauwmeijer et al (46) , o TCE é considerado a principal causa de morte e incapacidade em todo o mundo, especialmente em pessoas com idade inferior a 40 anos (120) .…”
Section: Variáveis Relacionadas àS Consequências Dos Acidentes De Trâunclassified